2011
DOI: 10.1902/jop.2011.100404
|View full text |Cite
|
Sign up to set email alerts
|

Intramarrow Bone Morphogenetic Protein 4 Gene Delivery Enhances Early Implant Stability in Femurs of Ovariectomized Rabbits

Abstract: The results of this study suggest that intramarrow adenoviral gene delivery of BMP4 enhances peri-implant bone healing and improves early implant stability in osteoporotic rabbit femurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In addition, a sustained release over time from a confined compartment not only assures a long-term ongoing osteogenic activity, but also provides maximum efficacy (being the delivery system directed specifically to the targeted cell pools) as well as mimics the physiological mode Dental implant healing in an osteopenic environment of growth factor release from the bone matrix during bone remodelling (Liu et al, 2018;Liu et al, 2005). Other approaches to deal with the enhancement and acceleration of bone formation and implant osseointegration under osteopenic/osteoporotic conditions have been described, such as the local delivery of BMP-4 (Lai et al, 2011), the use of injectable tricalcium phosphate (TCP)-microspheres associated with BMP-2 (Chang et al, 2017), the local application of anti-cytokine antibodies (Yang et al, 2020) or the use of systemic sclerostin antibody treatment (Korn et al, 2019;Virdi et al, 2015). Another approach suggested relates to the presurgical injection of BMP-7 in a slow-release system [polyglycolic acid (PLGA)-microspheres] to initially build up local bone structure before implant placement (Phillips et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a sustained release over time from a confined compartment not only assures a long-term ongoing osteogenic activity, but also provides maximum efficacy (being the delivery system directed specifically to the targeted cell pools) as well as mimics the physiological mode Dental implant healing in an osteopenic environment of growth factor release from the bone matrix during bone remodelling (Liu et al, 2018;Liu et al, 2005). Other approaches to deal with the enhancement and acceleration of bone formation and implant osseointegration under osteopenic/osteoporotic conditions have been described, such as the local delivery of BMP-4 (Lai et al, 2011), the use of injectable tricalcium phosphate (TCP)-microspheres associated with BMP-2 (Chang et al, 2017), the local application of anti-cytokine antibodies (Yang et al, 2020) or the use of systemic sclerostin antibody treatment (Korn et al, 2019;Virdi et al, 2015). Another approach suggested relates to the presurgical injection of BMP-7 in a slow-release system [polyglycolic acid (PLGA)-microspheres] to initially build up local bone structure before implant placement (Phillips et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Insertion of implants into the femoral condyle of New Zealand white rabbits represents a common model for osseointegration research within the field of dental implantology, mimicking submerged and unloaded healing conditions. Histomorphometric analysis of bone anchorage parameters revealed similar results, with slight advantages for Ti‐Sr‐O when looking at BIC%.…”
Section: Discussionmentioning
confidence: 99%
“…104 Lai et al found BMP-4 adenoviral gene transfer via the bone marrow promotes prior implant stability and peri -implant bone repair in osteoporotic rabbit femurs. 105 Kanzaki et al study of periodontal disease is effectively halted from continuing with the delivery of AAV2/1-TNFR:Fc, showing an additional method of inhibiting the generation of cytokines that are caused by pathogenic lipopolysaccharide. 106 The transfer of PDGF genes into animal cells and the subsequent increase in cementoblastic activity is an illustration of gene delivery.…”
Section: Biomolecule Delivery and Additive Manufacturing For Periodon...mentioning
confidence: 99%